Epidemiology, Environmental Risks, Virulence, and Resistance Determinants of Klebsiella pneumoniae From Dairy Cows in Hubei, China - Xiangyun Wu; Jiayi Liu; Jiawei Feng; Muhammad Abu Bakr Shabbir; Yali Feng; Rui Guo; Meifang Zhou; Sulin Hou; Guiqiang Wang; Haihong Hao; Guyue Cheng; Yulian Wang (2022)
Klebsiella pneumoniae (K. pneumoniae) is an opportunistic pathogen, which causes serious infections in humans and animals. To investigate the antimicrobial resistance pattern and virulence profile of K. pneumoniae, a total of 887 samples were collected from both the healthy and mastitis cows and the bedding, feed, feces, air, drinking water, spraying water, washing water, and milk cup swabs from five dairy farms in Hubei, China, during 2019 and 2020. K. pneumoniae was isolated and identified using PCR of the khe and 16S rDNA sequencing. A genotypic characterization was performed for K. pneumoniae isolates using wzi typing and multilocus sequence typing (MLST). Antimicrobial resistances were confirmed using broth microdilution against 17 antimicrobial agents and resistance and virulence genes were determined by PCR. The prevalence of K. pneumoniae was 26.94% (239/887) distributed in 101 wzi allele types (199/239, 83.26%) and 100 sequence types (STs) (209/239, 87.45%), including 5 new wzi allele type and 25 new STs. Phylogenetic analysis showed that K. pneumoniae isolated from milk, nipple swab, feed, and feces is classified in the same clone complex. By comparing with the PubMLST database, at least 67 STs have the risk of spreading in different species and regions. Interestingly, 60 STs have been isolated from humans. The isolates were highly sensitive to meropenem and colistin, but resistant to ampicillin (100%), sulfisoxazole (94.56%), cephalothin (47.28%), streptomycin (30.13%), and so on. Noteworthy, multidrug-resistant (MDR) rate was found to be 43.93% in this study. By PCR, 30 of 68 antimicrobial resistance (AMR) genes were identified; the prevalence rate of blaTEM, blaSHV, strA, strB, aadA1, and aac(6')-Ib-cr was more than 50%. Eleven CTX-M-producing K. pneumoniae were found. The detection rate of fimH, mrkD, uge, wabG, entB, iutA, iroN, and ureA was over 85%. This study reinforces the epidemiological importance of K. pneumoniae in food-producing animals in Hubei. The emergence and spread of environmental MDR K. pneumoniae may pose a potential threat to food safety and public health.